ANALYSIS METHOD AND PROCESS OPTIMIZATION OF VIBRATION SIGNAL IN PRECISION MILLING BASED ON BLIND SOURCE SEPARATION - GUO MiaoXian; HUANG Chao; GUO WeiCheng; WU ChongJun (Jixie qiangdu)
Precision milling technology has been widely used in the precision manufacturing in automobile, aerospace, microelectronics and other fields. Vibration during milling greatly affects machining accuracy and quality. In this paper, a method of cutting vibration signal analysis and optimization based on blind source separation is proposed in milling process. Firstly, combining Ensemble Empirical Mode Decomposition（EEMD） with Sparse Component Analysis（SCA）,the blind source separation of milling vibration signals was realized, so as to calculate the vibration contribution and analyze the main vibration factors of precision milling. Based on the analysis of vibration experimental signals, the order of influence of milling parameters on vibration was studied by Taguchi method. Finally, the optimization method of machining parameters is proposed.